PEMBUATAN GAME THIRD PERSON ENDLESS RUNNING “NO END RUN” DENGAN FITUR ACCELEROMETER DAN SHARE SCORE KE MEDIA SOSIAL - Fernando, Vicko; Pragantha, Jeanny; Haris, Darius Andana (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
No End Run is a 3D endless running game with the perspective of a third person and developed for Android smartphones. This game uses a touch screen and accelerometer sensor in the smartphone to control the character. As a running game, the character can run as far as possible, collect the collectables and avoid the monsters and obstacles. No End Run was made using the Unity game engine with C# as a programming language. Testing is done by Black Box testing, Alpha Testing and Beta Testing. The test results show that No End Run is an endless running game with interesting gameplay and has unique accelerometer controls so players are interested to play it again.